2023
DOI: 10.9734/bji/2023/v27i3683
|View full text |Cite
|
Sign up to set email alerts
|

Control Efficacy of Jingdusha against Corynespora cassiicola (Hyphomycetales: Dematiaceae) on Cucumber

Abstract: Aims: The paper aimed to clarify the effect of cucumber target leaf spot (TLS) under the Jingdusha (JDS) treatment. Study Design: We applied the method of artificial inoculation in the pot, and analyzed the changes in growth indexes and physiological characteristics. Place and Duration of Study: In 2018, these experiments were conducted in College of Bioscience and Biotechnology of Shenyang Agricultural University (Lab 240). Methodology: The seedlings in the two-leaf period were induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A previous study [6] found that JDS did not kill C. cassiicola by itself but had a significant resistance-inducing effect on cucumber seedlings. JDS at 2.0 mL•L -1 induced cucumber three times every 7 d interval for 1 d showed the highest efficacy of 68.93% against C. cassiicola [7]. To clarify the mechanism of resistance induction of cucumber TLS, we analyzed the changes of physiological and biochemical substances in cucumber plants after the optimal application program and then elucidated the mechanism of resistance induction of JDS to C. cassiicola.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [6] found that JDS did not kill C. cassiicola by itself but had a significant resistance-inducing effect on cucumber seedlings. JDS at 2.0 mL•L -1 induced cucumber three times every 7 d interval for 1 d showed the highest efficacy of 68.93% against C. cassiicola [7]. To clarify the mechanism of resistance induction of cucumber TLS, we analyzed the changes of physiological and biochemical substances in cucumber plants after the optimal application program and then elucidated the mechanism of resistance induction of JDS to C. cassiicola.…”
Section: Introductionmentioning
confidence: 99%